2021
DOI: 10.1007/s00170-021-07787-9
|View full text |Cite
|
Sign up to set email alerts
|

A generalized analysis of energy saving strategies through experiment for CNC milling machine tools

Abstract: This paper proposes the elaboration model of energy requirement prediction taking into account the power of standby, spindle rotation in non-load, feeding and rapid movement in X, Y, Z+ and Z-axially, and specific energy consumption (SEC) in the X and Y cutting directions respectively, which could not be considered completely in other models. Each part energy of specific machine tools could be obtained through little experiments for identifying the relationship between energy and tool path with cutting paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…These results are similar to those of Shi et al (2019), who also found that depth of cut was the most effective parameter for energy consumption. Similarly, Feng et al (2021) also observed that depth of cut was the most influential factor but found that the effects of a p and f were very close to each other. Figures 5 and 6 clearly illustrate that the depth of cut has a significant effect on the energy consumed and the machining cost, as there is a greater slope than the other two parameters.…”
Section: Prediction With the Rsmmentioning
confidence: 77%
“…These results are similar to those of Shi et al (2019), who also found that depth of cut was the most effective parameter for energy consumption. Similarly, Feng et al (2021) also observed that depth of cut was the most influential factor but found that the effects of a p and f were very close to each other. Figures 5 and 6 clearly illustrate that the depth of cut has a significant effect on the energy consumed and the machining cost, as there is a greater slope than the other two parameters.…”
Section: Prediction With the Rsmmentioning
confidence: 77%
“…The spindle sleeve moves up and down on the crossbeam of the milling machine through a guide rail, and the sliding saddle can drive the spindle sleeve to move horizontally left and right on the crossbeam, achieving the cutting motion of the milling machine. The crossbeam of the machine tool is mainly subjected to the cutting force of the tool, as well as the gravity of the saddle, spindle sleeve, and spindle itself [4]. From this, it can be seen that as key components on the milling machine, the crossbeam, saddle, and spindle sleeve of the milling machine bear most of the working load.…”
Section: Introductionmentioning
confidence: 99%